To Compare The Efficacy Of Trayodasanga Guggul And Mahamash Tail Matrabasti In Sandhigatavata W.S.R. To Osteoarthritis. - subhrajyoti, Chakraborty; Sukumar, Ghosh (International Research Journal of Ayurveda & Yoga, 2020)
Due to rapid urbanization and excessive workloads lifestyle becomes stressful and individuals suffer from various degenerative diseases. One such disease is Osteoarthritis whose prevalence ranges from 22 – 39% in India. Ageing and obesity are the major risk factors for its increased prevalence. In Ayurveda, it can be correlated with Sandhigata vata, a disease of vata origin which occurs due to vatavardhaka ahara vihara sevana and asthidhatu kshaya. The present study was conducted at Institute of Post Graduate Ayurvedic Education & Research, Shyamadas Vaidya Shastra Pith Hospital on 40 patients of sandhigata vata which was divided into two groups. Group A: 20 patients treated with Trayodashanga guggul in the dose of 500mg twice daily with dashamooladi kwath after meal for 1 month and Group B: 20 patients treated with Matrabasti by Mahamash taila(Niramish) for 21 days. The result was found to be highly significant in group B as compare to group A. Group of drugs in mahamash tail like Mash,Dashamula, Aswagandha,Rasana Shigru etc along with sneha plays an important role in subsiding the symptoms when applied per rectum as pakwashaya is the main site for vata dosha and aggravated vata dosh is responsible for this disease.So it acts as a key for overcoming this disease.